Revision of the genus Hylopachyiulus Attems, 1904, with a description of a new species from Croatia (Diplopoda, Julida, Julidae) - Antić, Dragan Ž.; Rađa, Tonći; Akkari, Nesrine (Zootaxa, 2018)
A revision of the julid genus Hylopachyiulus Attems, 1904 is given, and lectotypes and paralectotypes are respectively designated for the species H. corylorum (Verhoeff, 1907) and H. pygmaeus (Attems, 1904). We confirm the validity of H. pygmaeus and synonymize H. likanus Attems, 1926 syn. nov. under H. corylorum which is resurrected. Additonally, a third species is described from Croatia—H. ocellatus sp. nov.. Considerations on the taxonomic relationships in the tribe Pachyiulini and within the genus Hylopachyiulus are presented, and the distribution of its species is illustrated and discussed.